Vicissitudes na cobrança do crédito tributário e reflexos sobre o aprimoramento do processo executivo fiscal - Duque, Felipe Viana de Araújo (2019)
The purpose of this dissertation is to study the collection of the tax credit through the fiscal execution procedure, pointing out the vicissitudes of the system of conflict resolution and highlighting the necessary improvements to a fair, rapid and effective collection. It begins by re reading the classical dimension of the concept of taxation, considering the ethical perspective and the fundamental duty to pay taxes, as well as by going through the procedural instruments of the supposed privileged system in the collection of public credits that, in fact, guides to an enormous loss of social efficiency, mainly due to the excess of special installments routinely granted. The necessary improvements are highlighted, highlighting the need for unification and effective cooperation of the acts practiced in the administrative and judicial process, as well as for the fight against excess and disorganized judicial means of defense. It is proposed the viability of the previous administrative request as a condition to fill the interest of action to challenge the tax collection process judicially. The phenomenon of disjudicialization is presented as a paradigm in comparative law so that a rational and fair model of collection of public credits can be prepared. It ends by analyzing the appropriate methods of resolving tax disputes with democratization and citizen participation, notably arbitration and transaction, deepening efficient and strategic methods of extrajudicial collection of public debt, such as the recognition of interim Public administration.